2005
DOI: 10.4049/jimmunol.174.6.3518
|View full text |Cite
|
Sign up to set email alerts
|

A Splice Variant of the TCR ζ mRNA Lacking Exon 7 Leads to the Down-Regulation of TCR ζ, the TCR/CD3 Complex, and IL-2 Production in Systemic Lupus Erythematosus T Cells

Abstract: The reduction or absence of TCR ζ-chain (ζ) expression in patients with systemic lupus erythematosus (SLE) is thought to be a factor in the pathogenesis of SLE. We previously reported a splice variant of ζ mRNA that lacks the 36-bp exon 7 (ζ mRNA/exon 7(−)) and is accompanied by the down-regulation of ζ protein in T cells from SLE patients. In this study, we show that EX7− mutants (MA5.8 cells deficient in ζ protein that have been transfected with ζ mRNA/exon 7(−)) exhibit a reduction in the expression of TCR/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
3
22
1
Order By: Relevance
“…Also the decreased expression of certain genes could simply reflect reduced Ag-receptor mediated signaling intensity. We have already reported significantly reduced IL-2 production after anti-CD3 Ab treatment in both of these AS3Ј UTR and EX7Ϫ mutants (11,12). Our results in the study presented here showed downregulation not only of IL-2 but also of other ILs (IL-13, IL-15, and IL-18), chemokines (CCL3, CCL5, CCL9, XCL1), and a chemokine receptor (CCR7) in both the AS3Ј UTR and EX7Ϫ mutants, indicating that down-regulation of may lead to aberrant signal transduction followed by reduced expression of these cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Also the decreased expression of certain genes could simply reflect reduced Ag-receptor mediated signaling intensity. We have already reported significantly reduced IL-2 production after anti-CD3 Ab treatment in both of these AS3Ј UTR and EX7Ϫ mutants (11,12). Our results in the study presented here showed downregulation not only of IL-2 but also of other ILs (IL-13, IL-15, and IL-18), chemokines (CCL3, CCL5, CCL9, XCL1), and a chemokine receptor (CCR7) in both the AS3Ј UTR and EX7Ϫ mutants, indicating that down-regulation of may lead to aberrant signal transduction followed by reduced expression of these cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 81%
“…Expression of in the PBT of cancer patients or in tumor-infiltrating T cells has also been reported to be decreased (20 -23), and, interestingly, cytokine expression of IL-2 and IL-4 in these T cells has been observed to be down-regulated. DNA microarray analyses of the gene expression profiles of SLE patient T cells has revealed down-regulation of several TCRs, such as TCR␣␤, TCR␦, and TCR␥ (24 -26), indicating reduced expression of the TCR/CD3 complex in SLE patient T cells, the same as observed in the AS3Ј UTR and EX7Ϫ mutants (11)(12).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The reduction of the ζ chain levels, along with the reciprocal increase in the expression of FcRγ, is directly responsible for some of the phenotypic abnormalities characteristic of lupus T cells [10]. Accordingly, replenishment of the ζ chain leads to the down regulation of the FcRγ chain and subsequently to the correction of the TCR/CD3-induced increased calcium response and the abnormal phosphorylation of cellular substrates [11].…”
Section: Cd3ζ and Fcrγmentioning
confidence: 99%